Polydrug use patterns and their impact on relapse among heroin‐dependent patients in Shanghai, China. (31st October 2018) - Chen, Tianzhen; Zhong, Na; Du, Jiang; Li, Zhibin; Zhao, Yan; Sun, Haiming; Chen, Zhikang; Jiang, Haifeng; Zhao, Min
Abstract: Aims: To describe the polysubstance use patterns of heroin‐dependent patients and to understand the impact of polysubstance use patterns on relapse during the 5 years after completing compulsory rehabilitation programmes. Design: In this secondary analysis, the baseline data of 503 heroin‐dependent patients were linked with their 5‐year follow‐up data from official records. Setting: Four compulsory rehabilitation centres in Shanghai, China. Participants: A total of 564 heroin‐dependent patients who were discharged from Shanghai compulsory rehabilitation facilities in 2007 and 2008 were recruited. Among these, 503 patients with available follow‐up records were included in this analysis. Measurements: The baseline measurements included the Addiction Severity Index, the Temperament and Character Inventory and the Medical Outcomes Study Social Support Scale. Relapses after discharge from the compulsory rehabilitation centres were extracted monthly from the official electronic record system. Latent class analysis was used to identify different polysubstance use patterns. Associations between the identified latent classes and heroin use and the factors related to relapse during the 5‐year follow‐up were analysed with the Cox regression model. Findings: Three latent classes were identified in this cohort: (1) alcohol polydrug users (APU; 13.7%), (2) low polydrug users (LPU; 76.5%) and (3) amphetamine‐type stimulant polydrug users (ASPU; 9.7%). During the 5‐year follow‐up, 298 heroin patients relapsed, and the three groups showed different relapse rates (ASPU 69.4 versus LPU 60.5 versus APU 44.9%, P  = 0.02). The average durations of abstinence for the three groups differed (ASPU 31.27 ± 3.41 months versus LPU 36.77 ± 1.19 months versus APU 42.46 ± 2.81 months, P  = 0.02). Multivariate Cox regression analyses found that the LPU [hazard ratio (HR) = 1.63, 1.06–2.51] and ASPU (HR = 2.10, 1.24–3.56) classes were positively associated with the risk of heroin relapse. Conclusion: Polydrug use patterns differ among heroin‐dependent patients in compulsory rehabilitation programmes in China. A history of polydrug use may predict heroin relapse risk among patients in those compulsory rehabilitation programmes.